Antibiotics stimulate protein transfer to persister cells - Alice X. Wen; Julia Bos; Debojyoti Panda; Katelin M. Hagstrom; Shubham Singh; Shrawan Kumar Mageswaran; Xiaoli Wang; Bo Hu; Kobie T. Welch; Matthew B. Cooke; Jennifer A. Halliday; Laura Deus Ramirez; et al. (Science, 2026)
The exchange of biological matter between bacterial cells drives adaptation and evolution. However, whether bacteria can exchange functional proteins remains unclear. In this work, we found that antibiotic treatment can induce vesicle-mediated horizontal protein transfer within and between bacterial species. We developed a genetic system in Escherichia coli to track transfer events and performed single-cell transcriptomic profiling on an isogenic population of bacteria. Antibiotics stimulated the differentiation of this isogenic population into distinct cell states: donor cells that activated a membrane stress response to release protein-containing vesicles and recipient cells that suppressed this response to acquire protein from their neighbors. Protein uptake enhanced the antibiotic persistence of recipient cells, revealing that vesicle exchange promotes bacterial survival during antibiotic treatment.